2019
DOI: 10.3171/2017.12.jns172114
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided analysis of middle cerebral artery tortuosity: association with aneurysm development

Abstract: OBJECTIVE Blood vessel tortuosity may play an important role in the development of vessel abnormalities such as aneurysms. Currently, however, there are no studies analyzing the impact of brain blood vessel tortuosity on the risk of aneurysm formation. Therefore, the authors performed a computer-aided analysis of middle cerebral artery (MCA) tortuosity, especially among patients diagnosed with MCA aneurysms. METHODS Anatomy of the MCAs of 54 patients with unruptured MCA aneurysms was retrospectively analyzed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
4
8
1
Order By: Relevance
“…An interesting finding of this and our previous studies, in which we analysed tortuosity of MCA, ACA and ICA [12][13][14]25], are differences in contribution of certain tortuosity descriptors to risk of aneurysm development. For all four arteries, we found that increased values of TI were associated with higher risk of aneurysm presence.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…An interesting finding of this and our previous studies, in which we analysed tortuosity of MCA, ACA and ICA [12][13][14]25], are differences in contribution of certain tortuosity descriptors to risk of aneurysm development. For all four arteries, we found that increased values of TI were associated with higher risk of aneurysm presence.…”
Section: Discussionsupporting
confidence: 65%
“…It was shown before for aortic [10] and splenic artery [11] aneurysms. In terms of other cerebral vessels, a similar association was found for ICA [14,23], MCA [12], ACoA [13] and VA [24]. Additionally, increased tortuosity was associated with lower risk of intracranial aneurysm rupture [25] and inversely correlated with its size [13].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Methods of artery tracking and details about the software used for this study were described in our previous work [15]. For each patient’s DSA, we extracted a curve representing the ICA intracranial course (C2–C7 segments) and measured its Relative Length (RL), Sum of Angle Metrics (SOAM), Product of Angle Distance (PAD), Triangular Index (TI), and Inflection Count Metrics (ICM).…”
Section: Methodsmentioning
confidence: 99%
“…As tortuosity promotes hemodynamic changes in blood flow, it can lead to the development of aneurysms. Such association was found in terms of the aorta [11] and splenic artery [12], as well as in brain arteries, such as the internal carotid artery (ICA) [13], basilar artery (BA) [14], middle cerebral artery (MCA) [15], and vertebral artery [16]. Our previous study suggested that tortuosity of the anterior cerebral artery might play a role in anterior communicating artery aneurysm rupture [17].…”
Section: Introductionmentioning
confidence: 99%